Educational signaling under different education systems. - Ropero-García, Miguel Ángel (My University, 2024)
We consider a two-period signaling model in which an informed worker has to decide whether she invests in education or participates in the labor market in the first period. When the rate at which the cost of education decreases with the worker´s productivity is sufficiently high (low), the worker´s incentives to invest in education become stronger (weaker) when the worker is more patient, when future prospects in the labor market are better, or when the cost of education decreases. Those results are robust to the worker´s risk preferences and to the specification of the prior distribution function of worker´s productivities.
Since 1999 game theorists worldwide are organised in the Game Theory Society, which holds a World Congress every four years to promote the investigation, teaching, and application of game theory. Furthermore, there are two other worldwide important conferences on game theory, which take place on annual basis: The Stony Brook International Conference on Game Theory in the United States of America and the European Meeting on Game Theory (SING), being the most important conference in Europe.
Keywords: Reciclaje profesional; Juegos, Teoría de; Education; Risk preferences; Selective educational system; Separating equilibrium; Signaling